Comorbidity progression patterns of major chronic diseases: The impact of age, gender and time-window. (June 2023) - Uddin, Shahadat; Wang, Shangzhou; Khan, Arif; Lu, Haohui
Objective: The presence of one chronic disease often leads to the development of one or more other chronic diseases. This study examines whether there are significant progressions between chronic diseases and identifies the risk factors that influence them. Methods: This study used an administrative healthcare dataset sample from 29, 280 hospitalized patients over 24 years (1995 to 2018, inclusive) to explore the progression of common chronic diseases and their major comorbidities. An Australian health insurance organization provided the dataset. We used the t-test to examine the statistical significance of progression between chronic diseases. A network analysis approach is followed to rank different chronic diseases contributing to disease progressions. Results: We found that few chronic diseases (e.g. cardiovascular diseases and diabetes) have a high prevalence in progressing to other chronic diseases, which is statistically significant at p  ≤ 0.05. These progression frequencies significantly increase with time and age. We also found that patients' sex differently affects the disease progressions. Discussion: This study found that some chronic diseases have a high prevalence in comorbidity progressions. In addition, the progression statistics differ with time and age. The results of this study can help researchers, stakeholders, and policymakers gain insights into the disease transitions and act as a guiding tool to assess future disease burden and plan accordingly.